Ghrelin rescues skeletal muscle catabolic profile in the R6/2 mouse model of Huntington's disease. Issue 1 (December 2017) - Sjögren, Marie; Duarte, Ana; McCourt, Andrew; Shcherbina, Liliya; Wierup, Nils; Björkqvist, Maria
Abstract Accumulating evidence suggests altered energy metabolism as a key feature in Huntington's disease (HD) pathology. Hyper-catabolism, including weight loss and muscle atrophy, is seen in HD patients and HD mouse models. Metabolic hormones are key players, not only in energy metabolism, but also in neurodegenerative processes. Ghrelin, a gut peptide-hormone, plays an important role in regulating energy metabolism, stimulating appetite, and affects brain function and increases neuronal survival. The R6/2 mouse model of HD has previously been shown to exhibit progressive weight loss, dysregulated glucose metabolism, skeletal muscle atrophy and altered body composition. In this study, we targeted energy metabolism in R6/2 mice using ghrelin administration, with the primary aim to delay weight loss and reduce muscle atrophy. We also evaluated glucose metabolism and behaviour. We here demonstrate that ghrelin administration (subcutaneous 150 μg/kg daily injections) for 4 weeks, reversed the catabolic gene expression profile (increased expression ofCaspase 8, Traf-5 andCreb1 ) seen in R6/2 mouse skeletal muscle. Skeletal muscle morphology was also improved with ghrelin, and importantly, ghrelin administration normalized behavioural deficits in R6/2 mice. Taken together, our findings encourage further studies targeting metabolism in HD.